The Effect of Job Satisfaction on Employee Performance at Daima Hotel Padang - Rini Deswita; Waryono (Pt. Threeple Herphi Educate, 2025)
This study aims to determine the effect of job satisfaction on employee performance at Daima Hotel Padang. The research method used was quantitative research using the causal associative method. The population in this study was all 62 Daima Hotel Padang employees, who were selected as respondents using a saturated sampling technique. Data were collected through questionnaires and analyzed using SPSS version 29.00, using validity and reliability tests, and simple linear regression analysis. The results showed that employee job satisfaction was classified as good, with a score of 84.86%, while employee performance was also classified as good, with a score of 80.87%. Based on the results of the hypothesis test, the t-value was 5.953 with a significance level of 0.001 (<0.05), indicating that job satisfaction has a positive and significant effect on employee performance at Daima Hotel Padang. These results indicate that increased job satisfaction can directly impact employee performance and overall hotel service quality.